Spectroscopy of Cd2 and Zn2 molecules in free-jet supersonic beams: experimental and theoretical studies - Ruszczak, Marek; Strojecki, Marcin; Krośnicki, Marek; Łukomski, Michał; Koperski, Jarosław (Oficyna Wydawnicza Politechniki Wrocławskiej, 2006)
A method of supersonic beam combined with techniques of laser spectroscopy and simulations of spectra were employed to study interatomic potentials of Cd2 and Zn2 molecules. Total laser induced fluorescence was recorded after an excitation of Cd2 using laser radiation in the range of 2200–2260 angstrom. The observed structures are interpreted as due to the transitions from u" = 0 in the ground X10g+ state to vibrational levels below the potential barrier of the 11u(51P1) electronic state. Studies of Zn2 consisted of simulations of excitation and fluorescence spectra recorded at the 10u+(41P1)–X10g+ transition. In the simulations, both isotopic and rotational structures were taken into account.
Optica Applicata, Vol. 36, 2006, nr 4, s. 451-459
Keywords: optyka; cadmium dimer; zinc dimer; potential energy curves; ab initio potentials; excitation spectra; fluorescence spectra; van der Waals molecules; supersonic free-jet beam